2022
DOI: 10.3389/fnagi.2022.909273
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aging on animal models of Parkinson's disease

Abstract: Aging is the biggest risk factor for developing Parkinson's disease (PD), the second most common neurodegenerative disorder. Several animal models have been developed to explore the pathophysiology underlying neurodegeneration and the initiation and spread of alpha-synuclein-related PD pathology, and to investigate biomarkers and therapeutic strategies. However, bench-to-bedside translation of preclinical findings remains suboptimal and successful disease-modifying treatments remain to be discovered. Despite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 184 publications
1
14
0
Order By: Relevance
“…Agingrelated changes in mitochondrial and lysosomal pathways may contribute to increased disease susceptibility in aged animal models of disease. [2,69,70] While differences in the mitochondrial mass of enteric neurons from PD patients, and differences in expression of mitochondrial genes in PD colon biopsies have been previously reported [71,72], we see evidence for alterations in epithelial cells both from gene expression pro ling and respirometry in freshly isolated colon crypts. One possible functional consequence of these alterations is impaired intestinal homeostasis [73][74][75][76] resulting in reduced barrier integrity, which is seen in PD [57][58][59]61,63].…”
Section: Discussionsupporting
confidence: 54%
“…Agingrelated changes in mitochondrial and lysosomal pathways may contribute to increased disease susceptibility in aged animal models of disease. [2,69,70] While differences in the mitochondrial mass of enteric neurons from PD patients, and differences in expression of mitochondrial genes in PD colon biopsies have been previously reported [71,72], we see evidence for alterations in epithelial cells both from gene expression pro ling and respirometry in freshly isolated colon crypts. One possible functional consequence of these alterations is impaired intestinal homeostasis [73][74][75][76] resulting in reduced barrier integrity, which is seen in PD [57][58][59]61,63].…”
Section: Discussionsupporting
confidence: 54%
“…Our findings have important implications in both preclinical and clinical conditions. Most of previous studies used young animals to establish PD models, however, young animals are more resistant to PD‐related pathophysiology than old animals 45 . Therefore, animal models that better characterize clinical disease within the elderly would be more beneficial, as it will increase the translational value and attenuate the risk of failures in clinical trials 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of previous studies used young animals to establish PD models, however, young animals are more resistant to PD‐related pathophysiology than old animals. 45 Therefore, animal models that better characterize clinical disease within the elderly would be more beneficial, as it will increase the translational value and attenuate the risk of failures in clinical trials. 45 In fact, Miller et al 46 have ever found both aging and genetic susceptibility were required for the occurrence of disease phenotypes, such as loss of tyrosine hydroxylase (TH) expression and enlarged mitochondria or Lewy‐body‐precursor inclusions using a premature aging model by expressing progerin, a truncated form of lamin A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ageing and inflammation are among the key factors that may promote neuronal dysfunction and degeneration. 2,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]46,102 Notably, ageing, as a multistep chronic physiological process affecting central and peripheral organ and tissue homeostasis relies on highly integrated interactions, especially neuroendocrine-immune crosstalks, both at central and peripheral levels, that may turn into a pathological setting, as a result of dysfunctional genetic/epigenetic regulatory networks, as observed in PD 46,[102][103][104] .…”
Section: Discussionmentioning
confidence: 99%